2016
DOI: 10.1007/s00726-016-2173-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential of creatine or phosphocreatine supplementation in cerebrovascular disease and in ischemic heart disease

Abstract: Creatine is of paramount importance for maintaining and managing cellular ATP stores in both physiological and pathological states. Besides these "ergogenic" actions, it has a number of additional "pleiotropic" effects, e.g., antioxidant activity, neurotransmitter-like behavior, prevention of opening of mitochondrial permeability pore and others. Creatine supplementation has been proposed for a number of conditions, including neurodegenerative diseases. However, it is likely that creatine's largest therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 97 publications
4
36
0
1
Order By: Relevance
“…These predictions were borne out [98] (Fig. 6) and furthermore demonstrated that previous observations [102] concerning the sparing of synaptic transmission and neuronal excitability by creatine were not entirely due to better ATP-dependent support for neurotransmitter release per se, but by reduced extracellular adenosine release. Similar observations of RibAde and creatine facilitating and reducing adenosine release during seizure activity, with inhibitory and excitatory actions on neuronal activity, respectively, have been made in an in vitro model of epileptiform activity [103].…”
Section: Atp and Ogdsupporting
confidence: 65%
“…These predictions were borne out [98] (Fig. 6) and furthermore demonstrated that previous observations [102] concerning the sparing of synaptic transmission and neuronal excitability by creatine were not entirely due to better ATP-dependent support for neurotransmitter release per se, but by reduced extracellular adenosine release. Similar observations of RibAde and creatine facilitating and reducing adenosine release during seizure activity, with inhibitory and excitatory actions on neuronal activity, respectively, have been made in an in vitro model of epileptiform activity [103].…”
Section: Atp and Ogdsupporting
confidence: 65%
“…The CK/PCr energy shuttle thereby connects sites of ATP production (glycolysis and mitochondrial oxidative phosphorylation) with subcellular sites of ATP utilization (ATPases) in order to fuel energy metabolism [24, 25, 27]. In this way, the CK/PCr system thereby serves as an important regulator of metabolism which may help explain the ergogenic and potential therapeutic health benefits of creatine supplementation [4, 27, 33, 3645].
Fig.
…”
Section: Metabolic Rolementioning
confidence: 99%
“…Unfortunately, in clinical studies, creatine supplementation has shown no significant positive effects in chronic neurodegenerative diseases (see above). Balestrino et al (2016) surmise that creatine may be better suited for clinical interventions in more acute situations, where tissues undergo an energy deficit crisis, e.g. during ischemic stroke in the brain or myocardial ischemic attack leading to heart infarction.…”
Section: Creatine In Heart Function and Liver Pathologymentioning
confidence: 99%
“…However, since creatine would have to be energetically charged to PCr before it could develop its potential, and because the tissue in question is itself energy-depleted and thus cannot use its ATP to charge PCr, creatine should then be administered preventively to patients at high risk of stroke, even before the event takes place. An alternative approach, proposed and researched successfully by the group around Valdur Saks already in the 1980s (Ruda et al 1988) and followed up by Balestrino et al (2016), is that PCr is directly administered to patients by intravenous infusion as early as possible after an ischemic heart attack and during cardiac surgery. This strategy resulted in a significant improvement in cardiac parameters and subsequent prevention of cardiac arrhythmia, which is often also a problem after cardiac surgery.…”
Section: Creatine In Heart Function and Liver Pathologymentioning
confidence: 99%
See 1 more Smart Citation